Mathematical treatment of PDE model of chemotactic E. coli colonies - Celiński, R; Hilhorst, D; Karch, G; Mimura, M; Roux, P (Elsevier, 2021)
We consider an initial-boundary value problem for reaction-diffusion equations coupled with the Keller-Segel system from the chemotaxis theory which describe a formation of colony patterns of bacteria Escherichia coli. The main goal of this work is to show that global-in-time solutions of this model converge towards stationary solutions depending on initial conditions.